Prioritizing Critical Success Factors for Reverse Logistics as a Source of Competitive Advantage - Mpho Sharon Makaleng (Ital Publication, 2024)
Reverse logistics has received a lot of attention due to the negative impact it has on the environment and the growing demand for green products. This especially occurred in the fast-moving consumer goods retail sector due to recalls and waste management. This sector significantly contributes to the gross domestic product growth of all countries. This has therefore led to the growing significance of reverse logistics since the fast-moving consumer goods retail sector cannot avoid reverse logistics. The primary objective of this study was for fast-moving consumer goods retailers to prioritize critical success factors for reverse logistics as a source of competitive advantage in the fast-moving consumer goods retailers’ sector. This is because it is essential for the fast-moving consumer goods retail sector to implement critical success factors in reverse logistics that can lead to firm competitiveness. The study employed a positivist research philosophy, where data were collected from 418 fast-moving consumer goods retailers and consumers via SurveyMonkey using two close-ended questionnaires. The Statistical Package for the Social Sciences and the Analysis of Moment Structures software version 27 were employed to analyze the data. The results offer insight into the critical success factors in reverse logistics that should be carried out to achieve firm competitiveness. Through the implementation of critical success factors, this sector will achieve several goals, such as meeting environmental protocols, decreasing operational costs, cultivating the cumulative value of the brand, and improving customer satisfaction. Doi: 10.28991/ESJ-2024-08-02-018 Full Text: PDF